Upaya Union of European Football Associations (UEFA) dalam Mengatasi Rasisme Sepak Bola di Italia - Amri, Muh. Fiqry Ahsabannur; Bt. Mamma, Beche (Journal of International and Local Studies, 2024)
This research aims to determine UEFA's efforts to overcome cases of racism that occurred in Italian football in the 2017-2022 period. This research uses the concept of International Cooperation put forward by Robert Axelhord and Robert Keohane in answering the problem formulation. The research results show that the phenomenon of racism in Italy has been rooted for a long time because there is still an ideology attached to some Italian people. These acts of racism were carried out by unscrupulous supporters against black players. One of them is FARE since the early 2000’s, which has become UEFA's closest partner in fighting racism by issuing several regulations and of course anti-racism activities. In the 2017-2019 period, there were various incidents of racism in the Italian League, peaking in 2019 with several series of cases. In 2020, racist incidents in stadiums decreased drastically due to the Covid-19 pandemic. Incidents of racism continue to occur even though strict sanctions have been given and all campaigns have been carried out but they have not had a deterrent effect and a significant reduction in incidents of racism in the Italian league.